Zeroes of polynomials and entire functions in the works of N. Obreshkoff (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1997)
In the paper some of the most remarkable Obreshkoff's results about zero distribution of algebraic polynomials and entire functions of exponential type are discussed.